2021
DOI: 10.1021/acsami.1c13480
|View full text |Cite
|
Sign up to set email alerts
|

Focused Plasma- and Pure Water-Enabled, Electrode-Emerged Nanointerfaced NiCo Hydroxide–Oxide for Robust Overall Water Splitting

Abstract: Bimetallic, bifunctional electrocatalysts capable of driving both oxygen (OER) and hydrogen (HER) evolution half-reactions on both electrodes in commercial water electrolysis cells are among the most promising materials systems for clean hydrogen energy generation. However, insufficient hydrogen and oxygen production activity at industry-relevant current densities and long-term catalyst stability on the electrode surface prevent this approach from industrial translation. This work resolves these challenges by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…(F) Magnetic field‐enhanced, focused atmospheric‐pressure plasma jet system for synthesizing the electrode‐emerged nanointerfaced bimetallic hydroxide–oxide electrocatalysts. Reproduced with permission: Copyright 2021, American Chemical Society 92 . (G) Atmospheric‐pressure plasma jet (APPJ) system for the construction of nonstoichiometric ultrathin Ni x O y layers.…”
Section: Recent Advances Of Plasma‐modified Electrocatalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…(F) Magnetic field‐enhanced, focused atmospheric‐pressure plasma jet system for synthesizing the electrode‐emerged nanointerfaced bimetallic hydroxide–oxide electrocatalysts. Reproduced with permission: Copyright 2021, American Chemical Society 92 . (G) Atmospheric‐pressure plasma jet (APPJ) system for the construction of nonstoichiometric ultrathin Ni x O y layers.…”
Section: Recent Advances Of Plasma‐modified Electrocatalystsmentioning
confidence: 99%
“…Zhuang et al have reported an Ar plasma approach to synthesize Ir/Cu oxide nano‐clusters evenly on defective graphene as pH‐universal water splitting electrocatalysts 114 . Chen et al have utilized magnetic‐field focused plasma jets of atmospheric‐pressure O 2 /Ar (Figure 7F) to produce nano‐interfaced NiCo LDH nanosheets anchored with NiCo oxide nanoparticles for robust overall water splitting 92 . The high‐density Ar ions increase the reactive sites by etching following nucleation and growth of LDH and exposure to the O 2 /Ar plasma provides the reactive precursors for subsequent formation of bimetallic oxide spherical particles.…”
Section: Recent Advances Of Plasma‐modified Electrocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noted that the information about the instruments and detection methodology and parameters has been provided in our reported work. 24 Electrochemical Measurements. At room temperature, all electrochemical tests are performed by an electrochemical workstation (Model: CHI 660E, Shanghai Chenhua Instrument Co, Ltd) with an alkaline medium (1.0 M KOH), where the catalyst, Hg/HgO, and a carbon rod serve as the working, reference, and counter electrodes, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%